The future of auroral E-region plasma turbulence research - Huyghebaert, Devin; Billett, Daniel; Chartier, Alex; Chau, Jorge L.; Hussey, Glenn C.; Hysell, David L.; Ivarsen, Magnus F.; Mesquita, Rafael L. A.; Rojas, Enrique; Vierinen, Juha; Young, Matthew (Frontiers in Astronomy and Space Sciences, 2022)
The heating caused by ionospheric E-region plasma turbulence has documented global implications for the energy transfer from space into the terrestrial atmosphere. Traveling atmospheric disturbances, neutral wind motion, energy deposition rates, and ionospheric conductance have all been shown to be potentially affected by turbulent plasma heating. Therefore it is proposed to enhance and expand existing ionospheric radar capabilities and fund research into E-region plasma turbulence so that it is possible to more accurately quantify the solar- terrestrial energy budget and study phenomena related to E-region plasma turbulence. The proposed research funding includes development of models to accurately predict and model the E-region plasma turbulence using particle-in-cell (PIC) analysis, fluid-based analysis, and hybrid combinations of the two. This review provides an expanded and more detailed description of the past, present, and future of auroral E-region plasma turbulence research compared to the summary report submitted to the National Academy of Sciences Decadal Survey for Solar and Space Physics (Heliophysics) 2024-2033 (Huyghebaert et al., 2022a).